Mental Health and Wellbeing: Models and Modifications - Sharma, Dr Vikas; Banerjee, (Dr) Padmakali (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Mental health conceptualization has transformed from pathology oriented to growth oriented. The current research paper highlights the literature on the concept of mental health and wellbeing from various perspectives. The psychoanalytic, cognitive and behavioral school made significant contributions to the understanding of mental health and well being. The preventive aspects in mental health were underemphasized. The recent years have seen emergence of positive psychology school giving more importance to concepts of wellbeing from the perspective of growth. The optimism is examined in the context of mental and physical health. The optimism is a protective factor against mental health problems particularly depression and anxiety. Optimism is also associated with increased immune functioning in general and faster recovery from certain physical conditions.